2019
DOI: 10.1002/crat.201900171
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Electrostatic Potential Surface to Predict Supramolecular Synthons for RDX/Solvent Cocrystals

Abstract: Cocrystallization has attracted growing interests in the energetic field as it can tune properties by selecting and arranging existing molecules. Herein, the application of molecular electrostatic potential surface to predict supramolecular synthons for 1,3,5‐trinitro‐1,3,5‐triazinane (RDX)/solvent cocrystals is demonstrated. Six RDX/solvent supramolecular synthons are constructed and investigated by density functional theory. The results of Bader's atoms in molecules (AIM) and independent gradient model (IGM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Supramolecular explosive is highly organized aggregates of coordination saturated energetic molecules through noncovalent interaction [45] (hydrogen bonds, π‐π stacking, van der Waals forces, and halogen bonds, etc.). In recent years, related studies [46–50] have shown the importance of designing supramolecular explosives to balance the energy and stability of explosives. As a high‐energy and low‐sensitivity explosive, CL‐20 has a detonation velocity of 9400 m ⋅ s −1 and an impact sensitivity ( H 50 ) of 24 cm [43], while LLM‐105, as a representative insensitive explosive, has a detonation velocity of 7820 m ⋅ s −1 and an impact sensitivity of 117 cm [44].To coordinate the energy and sensitivity of the two explosives, 6 kinds of supramolecular explosives with CL‐20 and LLM‐105 as subject and object at a molar ratio of 1 : 1 were assembled.…”
Section: Resultsmentioning
confidence: 99%
“…Supramolecular explosive is highly organized aggregates of coordination saturated energetic molecules through noncovalent interaction [45] (hydrogen bonds, π‐π stacking, van der Waals forces, and halogen bonds, etc.). In recent years, related studies [46–50] have shown the importance of designing supramolecular explosives to balance the energy and stability of explosives. As a high‐energy and low‐sensitivity explosive, CL‐20 has a detonation velocity of 9400 m ⋅ s −1 and an impact sensitivity ( H 50 ) of 24 cm [43], while LLM‐105, as a representative insensitive explosive, has a detonation velocity of 7820 m ⋅ s −1 and an impact sensitivity of 117 cm [44].To coordinate the energy and sensitivity of the two explosives, 6 kinds of supramolecular explosives with CL‐20 and LLM‐105 as subject and object at a molar ratio of 1 : 1 were assembled.…”
Section: Resultsmentioning
confidence: 99%
“…Monte Carlo method has been widely used to predict the crystal structure from the molecular structure. [26,27] Dreiding force field has high accuracy [28] in predicting the properties of organic compounds. The obtained polymorphs were fully optimized with symmetry constraints using the DFTB-D3 method.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…The co-crystal screening method was used in this study [ 10 ]; from a supramolecular perspective, naproxen has an effective functional group (carboxyl group) to form intermolecular hydrogen bonds due to the carboxyl group can act as both hydrogen bond acceptors and hydrogen bond donors. Various CCFs with free carboxylic, hydroxyl or amine groups were selected as potential CCFs [ 24 , 25 ], and finally we successfully obtained two co-crystals of NPX with caprolactam (azepan-2-one, CPL) and oxymatrine ((4R,7aS,13aR,13bR)-10-oxododecahydro-1H,5H-dipyrido [2,1-f:3′,2′,1′-ij] [1,6]naphthyridine 4(41H)-oxide, OMT); moreover, CPL belongs to cyclic imide and OMT belongs to quinoxaline alkaloids. The good news is that OMT has a wide range of pharmacological effects, especially anti-inflammatory [ 26 ], which will produce synergistic pharmacological effects on naproxen.…”
Section: Introductionmentioning
confidence: 99%